RESOURCE SAVING IN CONSTRUCTION INDUSTRY WITH HIGHWAY BRANCH AS EXAMPLE - A. V. Roudensky (Модернизация, инновация, развитие, 2016)
Consumption of energy is an objective (independent on cost fluctuations) technical efficiency criterion of any construction or repair work. Highway/road (particularly bituminous pavement) sector is an important construction industry part. Bituminous road pavement construction consists of such components as excavation and preparation of basic materials, manufacture of mixes, ready mix laying/compacting and transportation of all materials. Average energy consumption for every bituminous pavement construction component is assessed. Approach to resource and energy saving presented in the article may be used in construction industry to develop and implement innovativetechnical and organizational solutions both of general application and for individual projects.